Evolution of Thoracosphaeroideae (Peridiniales, Dinophyceae) and a case of atavism in taxonomically clarified Chimonodinium lomnickii var. wierzejskii from the Polish Tatra Mountains. Issue 4 (2nd October 2022) - Kretschmann, Juliane; Žerdoner Čalasan, Anže; Knechtel, Johanna; Owsianny, Paweł M.; Facher, Eva; Gottschling, Marc
ABSTRACT: Character evolution in calcareous dinophytes and their relatives is poorly understood at present, particularly regarding the transformations of the epitheca. The precise taxonomic identity of Chimonodinium lomnickii var. (≡ Peridinium ) wierzejskii is unclear, but two different arrangements of the epithecal plate pattern have been reported. We studied dinophyte material collected across Central Europe, including the type localities of Peridinium wierzejskii (Polish Tatra) and Peridinium lomnickii var. punctulatum (Berlin), and investigated the morphology of eight monoclonal strains in detail. We further obtained rRNA sequences of the strains, including 27 new GenBank entries, for a molecular phylogenetic study using a representative taxon sample of the Thoracosphaeroideae. Five ITS ribotypes could be distinguished in Chimonodinium, but neither the distribution nor morphological differentiation seems to correlate with these ribotypes. An evolutionary transformation of the epitheca is inferred from the phylogenetic tree, with the predominant plate pattern found in C. lomnickii var. wierzejskii exemplifying the derived character state. However, the rare epithecal plate pattern of C. lomnickii var. wierzejskii represents the ancestral character state today found in, for example, Peridinium and Scrippsiella . This is an indication of an atavism, of which only very few cases are known from the microbial domain. The name Peridinium wierzejskii is taxonomically clarified by epitypification. HIGHLIGHTS Rare documentation of atavism in the microbial domain Deep morphology of strain established from type locality Molecular phylogenetics inferred from concatenated rRNA sequence data